2014
DOI: 10.1149/2.062403jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lithium Storage in TiO2(B) by6Li-NMR and X-Ray Diffraction Analysis

Abstract: Lithium storage in TiO 2 (B) was investigated by 6 Li magic-angle spinning (MAS) nuclear magnetic resonance (NMR) and exsitu X-ray diffraction (XRD) analysis combined with the entropy ( S) and galvanostatic intermittent titration technique (GITT) measurements. Lithium storage sites in TiO 2 (B) were characterized to be separated from four bands assigned to different lithium storage sites. Band A at 0 ppm vs. LiCl in the 6 Li NMR spectra and S measurements indicated that ionic lithium was stored at surface doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…Therefore, the low capacity of bulk TiO 2 -B is due to kinetics limitation, which is in line with experimental proposals. 8,14,15,23,24 The values reported in Figure 6a are for structures with fully optimized atomic coordinates and unit cells. To investigate the influence of unit cell optimization on our results, we have recalculated diffusion barriers of the most favorable pathways in Figure 6a by performing only atomic coordinate optimization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the low capacity of bulk TiO 2 -B is due to kinetics limitation, which is in line with experimental proposals. 8,14,15,23,24 The values reported in Figure 6a are for structures with fully optimized atomic coordinates and unit cells. To investigate the influence of unit cell optimization on our results, we have recalculated diffusion barriers of the most favorable pathways in Figure 6a by performing only atomic coordinate optimization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They proposed that nanowires with shorter diffusion length can compensate the slow Li self-diffusivity so that a larger number of Li atoms per unit volume can be incorporated/​removed in/​from nanowires than the bulk form of TiO 2 -B. Furthermore, a galvanostatic intermittent titration technique (GITT) measurement by Hoshina et al reported a significant lowering of diffusion coefficient in bulk Li x ­TiO 2 -B above a Li content of x = 0.7.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently,t he crystal, local, and electronic structures of TiO 2 (B) and their changes upon lithiation have been subjectt o intense research. [82][83][84][85] An interesting debate concerning the degree and order of filling of the three lithium sites (A1, A2, and C) and, thus, the role of open channels in the TiO 2 (B) structure has been going on among theoreticians. [34,[86][87][88][89] The computational studies indicated low Li migration energies for paths along the b-axisc hannel and the [001] direction, suggesting favorable Li-ion mobility.…”
Section: Progress On Tio 2 (B)mentioning
confidence: 99%
“…In general, however, it is difficult to compare the absolute D values of TiO 2− x ‐C NTs and other TiO 2 polymorphs, because D is known to vary depending on the measuring method and the sample morphology. For instance, D values of anatase TiO 2 have been reported from 10 −12 to 10 −18 cm 2 s −1 . This is especially critical for the calculation of D in the low‐potential region in which Si is lithiated as the morphology changes substantially because of the strong expansion in the volume of the Li–Si alloy (Figure f) .…”
Section: Resultsmentioning
confidence: 99%